Design and analysis of piles subjected to negative skin friction - Tan, Chin Gee. (2009)
Settlement of the surrounding soil due to surcharge placement may give rise to negative skin friction developed in piles. Current design procedures are based on a semi-empirical assessment of field test data and no consistent theory is available to enable soil deformations to be taken fully into account. The design of pile foundations subjected to negative skin friction still remains controversial with regard to the maximum allowable working load. This is attributed to the limited understanding of the actual soil-structure interaction mechanisms of piles driven in soft compressible clays.